2020
DOI: 10.1186/s12978-020-0854-y
|View full text |Cite
|
Sign up to set email alerts
|

Oligohydramnios: a prospective study of fetal, neonatal and maternal outcomes in low-middle income countries

Abstract: Background: Oligohydramnios is a condition of abnormally low amniotic fluid volume that has been associated with poor pregnancy outcomes. To date, the prevalence of this condition and its outcomes has not been well described in low and low-middle income countries (LMIC) where ultrasound use to diagnose this condition in pregnancy is limited. As part of a prospective trial of ultrasound at antenatal care in LMICs, we sought to evaluate the incidence of and the adverse maternal, fetal and neonatal outcomes assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
42
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 21 publications
8
42
0
1
Order By: Relevance
“…In our study we found that, oligohydramnios was less in SPPH group than non-SPPH group. Sarah Crimmins reported that polyhydramnios increased the risk of PPH 21 and Lester Figueroa et al reported that oligohydramnios was the risk factor of PPH 22 . We also found that with the interval between two CDs more than 4 years, the longer the time was, the greater the possibility of SPPH was.…”
Section: Discussionmentioning
confidence: 99%
“…In our study we found that, oligohydramnios was less in SPPH group than non-SPPH group. Sarah Crimmins reported that polyhydramnios increased the risk of PPH 21 and Lester Figueroa et al reported that oligohydramnios was the risk factor of PPH 22 . We also found that with the interval between two CDs more than 4 years, the longer the time was, the greater the possibility of SPPH was.…”
Section: Discussionmentioning
confidence: 99%
“…Another study depicted more incidence of caesarean section, haemorrhage and fetal malposition in women with oligohydramnios than those having normal AFV. It also revealed higher occurrence of intrauterine deaths, neonatal demise and low birth weight 22,8 . Our findings were a higher rate of operative delivery, occurrence of meconium, umbilical arterial blood acidosis and low APGAR scores in pregnant women with oligohydramnios.…”
Section: Discussionmentioning
confidence: 92%
“…Local centers and secondary care setups treat a large number of gynecology and obstetrics (GYOB) patients in the developing world [ 18 ]. All housewives in our cohort were referred from the GYOB departments.…”
Section: Discussionmentioning
confidence: 99%